Cognitive Justice and Indigenous Knowledge Systems in the Postcolonial Classroom - Muchenje, Francis (Re-thinking Postcolonial Education in Sub-Saharan Africa in the 21st Century, 2017)
The question of the relevance of the school curriculum has been a subject of contentious debate in a number of Sub-Saharan African (SSA) countries, and was even included in the 2000 Millennium Development Goals (MDGs), which were supposed to be fulfilled by 2015. Critics have maintained that Africa is unable to benefit meaningfully from the investment made in education in the absence of a school curriculum that accommodates learners’ cultural backgrounds in the form of indigeneous knowledge systems (IKSs).